Syndromes associated with holoprosencephaly - Paul Kruszka; Maximilian Muenke (2018)
Holoprosencephaly (HPE) is partial or complete failure of the forebrain to divide into hemispheres and can be an isolated finding or associated with a syndrome. Most cases of HPE are associated with a syndrome and roughly 40%–60% of fetuses with HPE have trisomy 13 which is the most common etiology of HPE. Other syndromes associated with HPE include additional aneuploidies like trisomy 18 and single gene disorders such as Smith–Lemli–Opitz syndrome. There are a number of syndromes such as pseudotrisomy 13 which do not have a known molecular etiology; therefore, this review has two parts: syndromes with a molecular diagnosis and syndromes where the etiology is yet to be found. As most HPE is syndromic, this review provides a comprehensive list and description of syndromes associated with HPE that may be used as a differential diagnosis and starting point for evaluating individuals with HPE.